PENGEMBANGAN MEDIA FILM KARTUN PADA MATA PELAJARAN EKONOMI - Fatma Rossa; Pargito Pargito; R Gunawan Sudarmanto (Jurnal Studi Sosial / Journal of Social Studies, 2014)
This research aimed to develop learning media cartoon movies in economics and tested the effectiveness by comparing the pre test and post test average score of learning result between experimental class and control class. This research began with need assessment, the development of learning media and product test on students. From the result of research development, it can be concluded: the result of need assessment made the writer to develop cartoon movie media in economics, economics learning in experimental class which was given treatment by using cartoon movie media was more effective than control class which was not given  cartoon movie media, based on the result of t test, the effectiveness formula and classical accomplishment comparison that cartoon movie media on economics could be stated effective.Penelitian ini bertujuan untuk mengembangkan media pembelajaran film kartun pada mata pelajaran ekonomi serta menguji efektifitas dengan membandingkan rata-rata nilai pre-test dan post-test hasil belajar ekonomi antara kelas eksperimen dan kelas kontrol. Penelitian ini diawali dengan need asessment, pengembangan media pembelajaran dan pengujian produk pada peserta didik. Hasil penelitian need assesment mengugagah peneliti untuk mengembangan media film kartun pada mata pelajaran ekonomi, pembelajaran ekonomi pada kelas eksperimen yang diberi perlakuan dengan menggunakan media film kartun lebih efektif dari pada kelas konrol yang tidak menggunakan media film kartun, hasil perhitungan uji t, rumus efektifitas dan perbandingan ketuntasan klasikal menunjukan bahwa media film kartun pada mata pelajaran ekonomi dapat dikatakan efektif. Kata kunci: ekonomi, media film kartun, pengembangan